To the eastern seas - Stockwin, Julian (Stockwin, Julian. Kydd series, 2019)
"With Bonaparte held to a stalemate in Europe, the race to empire is now resumed. Britain's ambitions turn to the Spice Islands, the Dutch East Indies, where Admiral Pellew has been sent to confront the enemy's vastly rich holdings in these tropical islands. Captain Sir Thomas Kydd joins reinforcements to snatch these for the British Crown. The two colonial masters of India and the East Indies face each other in mortal striving for the region - there can be only one victor to hold all the spoils. The colonial genius, Stamford Raffles, believes Britain should strike at the very centre of Dutch spice production, the Moluccas, rather than the fortresses one by one but is fiercely opposed. Kydd, allying himself to this cause, conspires to lead a tiny force to a triumphant conclusion - however the Dutch, stung by this loss, claim vengeance from the French. A battle for Java and an empire in the East stretches Kydd and Tyger's company to their very limits."--Publisher